Rare case of infective aortitis with aortic rupture and cardiac tamponade in a young child. Issue 12 (1st December 2022) - Datta, Manas; Pradeep, Sangeetha; Aditya, Mainak
Abstract : Aortitis and aortic dissection are very rare in children. The clinical presentation of aortitis varies across a spectrum, ranging from incidental findings to fatal aortic dissection and rupture. A high index of suspicion is needed to establish an accurate and timely diagnosis. Here, we present an unfortunate case of fatal infective aortitis with aortic rupture and cardiac tamponade in a healthy toddler. Postmortem report implicated Kingella kingae as the causative organism of aortic pseudoaneurysm and rupture, leading to the instantaneous death of the child.